Principles of turbomachinery in air-breathing engines - Baskharone, Erian A. 1947-; Hill, D. Lee 1961- (New York Cambridge University Press, 2023)
"Acquire complete knowledge of the basics of airbreathing turbomachinery with this hands-on practical text. This updated new edition for students in mechanical and aerospace engineering discusses the role of entropy in assessing machine performance, provides a review of flow structures, and includes an applied review of boundary layer principles. New coverage describes approaches used to smooth initial design geometry into a continuous flow path, the development of design methods associated with the flow over blade shape (cascades loss theory) and annular type flows, as well as a discussion of the mechanisms for the setting of shaft speed. This essential text is also fully supported by over 200 figures, numerous examples, and homework problems, many of which have been revised for this edition."
Electronic reproduction.
Keywords: Gas-turbines.; Turbomachines; Electronic Resource